The Influence of Financial Crime on Tax Compliance: Moderating Effect of Government’s Future Orientation - Zahra Jihadia El Fitria Ramadhani; Ari Budi Kristanto (UNIB Press, 2022)
Taxes have become the primary source of revenue for most countries all over the globe. However, financial crime occurs in many parts of the world and may threaten this critical role of tax. This research aims to examine the influence of financial crime on tax compliance with the future orientation of the government as a moderating variable. This research is a cross-country research with a population of countries in the world. By using purposive sampling, the sample of this research is 105 countries. This research obtained secondary data to measure the country-level financial crime, tax compliance, and the government’s future orientation. To test the hypothesis, the data is then analyzed using moderated regression analysis (MRA). The results indicate that financial crime has a negative influence on tax compliance. Financial crimes can undermine a culture of compliance which can reduce tax compliance. The higher the financial crime, the lower the tax compliance. Furthermore, the future orientation of government can weaken the negative influence of financial crime on tax compliance. When the government has a future orientation that shows the government’s ability to prepare for the future for its welfare, people will tend to trust the government. The higher the trust, the higher the tax compliance so that government can still strive for tax compliance. This research contributes to providing information for the government in determining orientation strategies in response to the conditions of financial crimes that occur so that the government can still strive for tax compliance to maintain government revenue. The study's shortcomings include that it used data from many sources and years. As a result, readers should use caution when interpreting the research's findings, and the subsequent researchers should get data from the same year